The average rate of change of a function in the interval [a,b] is given by:
![m=(f(b)-f(a))/(b-a)](https://img.qammunity.org/2023/formulas/mathematics/high-school/8hvlpa2jmmqw5afqk4imwcy8fk7bijobyj.png)
In this case we know that the interval is [-1,3] which means that a=-1 and b=3. This also means that we need to find f(-3) and f(-1); from the table we have:
![\begin{gathered} f(-1)=(1)/(3) \\ f(3)=27 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/ocilnm97fn6jgcep413b55xb89erktkgs0.png)
Once we know all the values, we need we plug them in the expression for the average rate of change:
![\begin{gathered} m=(f(3)-f(-1))/(3-(-1)) \\ =(27-(1)/(3))/(3+1) \\ =((81-1)/(3))/(4) \\ =((80)/(3))/(4) \\ =(80)/(12) \\ =(20)/(3) \\ =6.67 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/7yrzvk38q1bdbaduq8992qa2dv2zmsec7i.png)
Therefore, the average rate of change of the function in that interval is 6.67.